Análogo hídrico-elétrico da estrutura foliar do Phaseolus vulgaris L. : o processo de transpiração - Rosa, Lauro Leocadio da (2020)
The process of leaf sweating is linked to the soil and environmental conditions that the plant is subjected to. A model of the leaf transpiration process should therefore consider plant physiology and edaphoclimatic conditions. Thus, the hydric-electric analog model developed in this work focuses on the physiology of the leaf of common black bean (Phaseolus Vulgaris L.) and on the values and variations of soil water quantity, temperature and relative humidity. For the development of the model, an experiment was implemented with the cultivation of Phaseolus Vulgaris L., drought period, at the “Mestre Bombled” weather station located at the Federal University of Mato Grosso, Cuiabá campus, composed by 198 feet, divided into 15 treatments. with different amounts of water in the soil. The data obtained from water flow, leaf water quantity, leaf area, stomatal density, average epidermal and stomatal cell area, as well as micrometeorological variables, in the day of the experiment, were used to modeling the hydric-electric analog circuits of the different paths that the liquid water or vapor follows by the leaf in the transpiration process. The circuit simulation was performed using the QUCS electrical circuit analysis software. The circuits were interconnected according to the leaf physiology of Phaseolus Vulgaris L. described in the literature, giving rise to a minimal unit of analysis of leaf sweating, called Mod_1. Using replicas of Mod_1 larger modules were built and organized in layers around this central one. In central Mod_1 is located the central ostiole by which the water flow was measured. After statistical analysis, it was observed that the simulated water flows had a strong direct correlation with the flows obtained in the experiment. By incrementing the replicates with Mod_1 by inference until it covers the whole of a leaf, the model continued to present the same statistical response, showing to be scalable. The results indicate that the model may be a tool for developing new studies on transpiration and its implications.